Australian Indigenous early career researchers: unicorns, cash cows and performing monkeys. Issue 1 (2nd January 2023) - Locke, Michelle; Trudgett, Michelle; Page, Susan
ABSTRACT: Data from the Developing Indigenous Early Career Researchers (ECRs) project reported that efforts of Indigenous ECRs are often undermined by examples of micro-racism. Shared personal experiences revealed racist attitudes and assumptions held by some non-Indigenous academics. This draws critical attention to the fact that while many institutions have developed Indigenous strategies to address disparities between Indigenous and non-Indigenous staff and student's, racism is prevelant in higher education institutions across Australia. In this study, Indigenous ECRs metaphorically described their presence in the academy as unicorns, cash cows or performing monkeys. These terms illustrate the way in which Indigenous ECR attendance in the Australian higher education sector has been viewed, devalued and/or undermined by non-Indigenous academics and the institutions in which they are employed. Specifically, the notion of behavioural racism is used to critique the level of engagement and commitment of non-Indigenous academics to the inclusion of Indigenous knowledges and worldviews.